Phosphorylation of Pnut in the Early Stages of Drosophila Embryo Development Affects Association of the Septin Complex with the Membrane and Is Important for Viability. Issue 1 (1st January 2018) - Akhmetova, Katarina; Balasov, Maxim; Svitin, Anton; Chesnokova, Elena; Renfrow, Matthew; Chesnokov, Igor
Abstract: Septin proteins are polymerizing GTPases that are found in most eukaryotic species. Septins are important for cytokinesis and participate in many processes involving spatial modifications of the cell cortex. In Drosophila, septin proteins Pnut, Sep1, and Sep2 form a hexameric septin complex. Here, we found that septin protein Pnut is phosphorylated during the first 2 hr of Drosophila embryo development. To study the effect of Pnut phosphorylation in a live organism, we created a new Drosophila pnut null mutant that allows for the analysis of Pnut mutations during embryogenesis. To understand the functional significance of Pnut phosphorylation, Drosophila strains carrying nonphosphorylatable and phospho-mimetic mutant pnut transgenes were established. The expression of the nonphosphorylatable Pnut protein resulted in semilethality and abnormal protein localization, whereas the expression of the phospho-mimetic mutant form of Pnut disrupted the assembly of a functional septin complex and septin filament formation in vitro . Overall, our findings indicate that the controlled phosphorylation of Pnut plays an important role in regulating septin complex functions during organism development.